Hot Melt Extrusion-Triggered Amorphization as a Continuous Process for Inducing Extended Supersaturable Drug Immediate-Release from saSMSDs Systems - Huan Yu; Yanfei Zhang; Yinghui Ma; Huifeng Zhang; Chengyi Hao; Yong Zhang; Zhengqiang Li; Xianrong Qi; Nianqiu Shi (Pharmaceutics, 2022)
Hot melt extrusion (HME), a continuous manufacturing process for generating supersaturating amorphous self-micellizing solid dispersion systems (saSMSDs), holds promise for achieving amorphization of many pharmaceutical formulations. For saSMSDs generation, HME-triggered continuous processes offer advantages over traditional non-continuous processes such as fusion/quench cooling (FQC) and co-precipitation (CP). Here we employed HME, FQC, and CP to generate saSMSDs containing the water-insoluble BCS II drug nitrendipine (NIT) and self-micellizing polymer Soluplus®. Scanning electron microscopy, powder X-ray diffraction, and differential scanning calorimetry results revealed that saSMSDs formed when NIT–Soluplus® mixtures were subjected to the abovementioned amorphization methods. All saSMSDs outperformed crystalline NIT preparations and physical mixtures in achieving extended supersaturable immediate release states with superior solubility, “spring-parachute” process characteristics, and dissolution behaviors. Notably, Fourier transform-infrared spectroscopic results obtained for saSMSDs detected hydrogen bonding interactions between the drug and the carrier. Ultimately, our results revealed the advantages of HME-triggered amorphization as a continuous process for significantly improving drug dissolution, increasing solubility, and maintaining supersaturation as compared to traditional amorphization-based techniques.